RANCANG BANGUN SISTEM MANAJEMEN LEGAL DRAFTING UNTUK MENDUKUNG TERTIB ADMINISTRASI - Dedeh Supriyanti; Andri Cahyo Purnomo; Ari Ismudiarti (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
Legal drafting is the formation of legislation which is the making of legislation that covers the stages of planning, drafting, discussing, ratifying or stipulating and promulgating. In its implementation, at the planning stage sometimes there are some things that are overlooked, so that they are not included in the drafting stage, as well as at the preparation stage, sometimes found several things that should not have been carried out or carried out at the discussion stage, this happened because of the high level of manualization and archiving. so it is very difficult in carrying out data collection on everything that has been done or that has not been done. Based on the things mentioned above, it is necessary to establish a system that is good in terms of the preparation of regulatory information systems so that mechanisms can be established to formulate regulations based on information management technology to help implement the tasks and functions of the sub-division of legislation. To be able to complete this,the author uses several methods, starting from the method of analyzing data and documents, then poured in the form of a design using uml, and stored in a database using MySql, which is implemented using the PHP programming language. the expected results are the creation of orderly administrative regulations to document regulations and decisions (beschikking) that are well-organized and documented.